Project-Based Learning Model on Mathematical Concept Understanding Ability in Mathematics Learning in Elementary Schools - Supriatna, Irfan; Ramadhani, Muhammad Habib; Asmahasanah, Salati (International Conference on Elementary Education, 2025)
This study seeks to assess the impact of the Project-Based Learning model on the mathematical comprehension skills of fifth-grade elementary students. This research methodology employs a quasi-experimental pretest-posttest group design. The study's population comprised fifth-grade children from SDN 60 Bengkulu City, with class VA serving as the control group of 22 individuals and class VB as the experimental group of 21 individuals. The research tool employed was a mathematics comprehension assessment. Analytical methods using descriptive statistics, prerequisite assessments, and t-tests. The study's results indicated a disparity in the average posttest scores, with the control class averaging 57.86 and the experimental class averaging 77.90, demonstrating that the mathematical comprehension of students in the experimental class exceeded that of the control class (77.90 > 57.86). The findings are derived from the table of distribution values for df = 41 (alpha = 5%) = 1.68. The computed t value exceeds the critical t value (5.786 > 1.68) and significance level. p-value (2-tailed) = 0.000 < 0.005. The null hypothesis (H0) is rejected, and the alternative hypothesis (H1) is accepted. The conclusion is that the Project-Based Learning model significantly influences the mathematical comprehension abilities of elementary school students.